PoligonSoft for foundry - A. V. Monastyrsky; Yu. B. Vlasov (Литьë и металлургия, 2022)
The article describes the system of casting computer simulation software PoligonSoft. The main features of the system and work stages are described. Particular attention is paid to the features of the latest version of the software product: what’s new in the flow and stress solvers, what’s new in the preprocessor and mesh generator. The analysis of the convergence of the simulation results and the collection of experimental data was carried out.